Persepsi Peserta Pertukaran Mahasiswa Merdeka Tentang Pelaksanaan Program Pertukaran Mahasiswa Merdeka MKBM - Khasanah, Winda Latifatul; Marliyah, Lili (Journal of Economic Education and Entrepreneurship, 2025)
This article aims to determine the perceptions of the 2nd batch of Independent Student Exchange (PMM) participants regarding the implementation of PMM MBKM; as well as the obstacles and solutions faced by PMM class 2 participants. This type of research uses descriptive methods with a qualitative approach. The research was conducted with 9 informants consisting of participants and Ivet University officials. The data analysis technique uses triangulation from the results of interviews, questionnaires, observation and documentation. The research results showed that: 1. In the preparation and introduction phase of the program, participants found out through digital media and understood the definition and concept of the program well, participants thought that the socialization stage was not optimal; 2. Recruitment phase, participants think that the preparation of files and use of the application is done well and is easy to do; 3. Implementation phase, a. The student's academic learning process is carried out in a hybrid manner by following academic rules assisted by the PIC, discussing with the Head of Study Program in taking courses, taking courses online at the Home University due to differences in credit weights, the main assessment system is attendance, the student quota for each course is fulfilled as much as 25-30 students, b. Nusantara Module activities are carried out by visiting regional tourist locations, inspirational activities presenting community leaders, reflection activities making video projects and writing impressions and messages, social contribution activities by helping local communities in solving problems; 4. Follow-up phase, participants do not fully know the conversion process, participants' perceptions are good and they recommend the program to other students. Obstacles and solutions for implementing PMM 2, namely socialization which will change the pattern and conversion flow, will be addressed with the Chancellor's Decree and looking for alternative solutions.